2020
DOI: 10.1515/ling-2020-0182
|View full text |Cite
|
Sign up to set email alerts
|

Children’s non-adultlike interpretations of telic predicates across languages

Abstract: The acquisition literature has documented several different types of misinterpretations of telic sentences by children, yet a comprehensive analysis of these child interpretations has not been attempted and a crosslinguistic perspective is lacking. This task is not easy, for, on the surface, children’s non-adultlike interpretations appear to be scattered and even contradictory across languages. Several cognitive biases have been proposed to explain given patterns (children initially adhere to a Manner bias, or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 93 publications
1
8
0
Order By: Relevance
“…This finding casts doubt on the hypothesis that children's interpretation errors with change-of-state and incremental theme verbs have a non-linguistic origin. The results are consistent with previous accounts that attributed these errors to eventlanguage mappings in children's acquisition of verb meanings, such as Martin et al (2020), who recently reviewed a large body of work on children's errors with changeof-state and incremental theme verbs and concluded that these errors are due to language-specific learning challenges. By adding evidence from a non-linguistic task and showing the same pattern for two different event types, we further strengthen their conclusion that non-linguistic conceptual biases may not be to blame.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This finding casts doubt on the hypothesis that children's interpretation errors with change-of-state and incremental theme verbs have a non-linguistic origin. The results are consistent with previous accounts that attributed these errors to eventlanguage mappings in children's acquisition of verb meanings, such as Martin et al (2020), who recently reviewed a large body of work on children's errors with changeof-state and incremental theme verbs and concluded that these errors are due to language-specific learning challenges. By adding evidence from a non-linguistic task and showing the same pattern for two different event types, we further strengthen their conclusion that non-linguistic conceptual biases may not be to blame.…”
Section: Discussionsupporting
confidence: 90%
“…By adding evidence from a non-linguistic task and showing the same pattern for two different event types, we further strengthen their conclusion that non-linguistic conceptual biases may not be to blame. Instead, it is likely that children struggle as they explore the typological spaces in which their language might reside (e.g., Talmy, 1991), as well as the complexity of how completion is realized in tense/aspect marking across languages (e.g., Martin et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After Verkuyl (1972), there is no doubt about encoding boundedness through articles, determiners, quantifiers, etc., and non-boundedness through their absence. But how these entities trigger boundedness and their absence non-boundedness remains undescribed (Czardybon and Fleischhauer 2014, Fleischhauer and Czardybon 2016, Filip 2017, Ihsane 2020, Martin et al 2020. Verkuyl (1993Verkuyl ( , 2022 explains it using formal semantic analyses; Kabakčiev's (2000; model uses temporality of situation participants as an approach.…”
Section: On the Essence And Intricacy Of Camentioning
confidence: 99%
“…After Verkuyl (1972), there is no doubt about encoding boundedness through articles, determiners, quantifiers, etc., and non-boundedness through their absence. But how these entities trigger boundedness and their absence non-boundedness remains undescribed (Czardybon and Fleischhauer 2014, Fleischhauer and Czardybon 2016, Filip 2017, Ihsane 2020, Martin et al 2020. Verkuyl (1993Verkuyl ( , 2022 explains it using formal semantic analyses; Kabakčiev's (2000;2019) model uses temporality of situation participants as an approach.…”
Section: On the Essence And Intricacy Of Camentioning
confidence: 99%